CREATION OF LOOPHILISATE OF GK-2 FOR PREPARATION OF SOLUTION FOR INJECTIONS WITH USE OF POLYOLS - E. V. Blynskaya; S. V. Tishkov; K. V. Alekseyev; S. V. Minaev (Разработка и регистрация лекарственных средств)
As part of the development of the composition and technology of the lyophilized dosage form with the pharmaceutical substance (FS) GK-2, which possesses neuroprotective activity, model compositions and technological properties are studied with different temperature regimes of production. In connection with the peptide structure and low stability of the FS, the use of excipients stabilizing dosage form during the lyophilization cycle (cryoprotectants and lyoprotectors) was suggested. In this study, we selected the ratios of cryo- and lyoprotectors when using mannitol or sorbitol as a cryoprotectant, and as a lyоprotector for sucrose. Model compositions with different exipients ratios were studied by optical microscopy in polarized light to demonstrate the physical state of mannitol at different ratios of explosives. Using the Harrington generalized desirability function, the most optimal composition is chosen, which meets the requirements of SF XIII and has the most acceptable technological characteristics and optimal technological process.